Synthesis and characterization of Cu(II), Co(II), Ni(II), and Zn(II) complexes of a Schiff base derived from 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one and 3-hydroxysalicylaldehyde - Sönmez, M; Levent, A; Sekerci, M (Taylor & Francis Inc, 2003)
Cu(II), Co(II), Ni(II) and Zn(II) metal complexes of a new beterocylic Schiff base derived from 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-one with 3-hydroxy-salicylaidehyde have been synthesized and characterized on the basis of elemental analyses, electronic, IR and H-1 NMR spectra, molar conductivity measurements, magnetic moment measurements and thermogravimetric analyses (TGA). It has been found that the Schiff base behaves as a neutral bidentate (NO) or tridentate (ONO) ligand forming chelates with 1:2 (metal:ligand) stoichiometry and octahedral geometry. The conductivity data for the Ni(II) complex is consistent with that expected for a weak electrolyte.
Keywords: N-aminopyrimidine; 3-hydroxysalicylaldehyde; metal complexes